A rare case of cystic lymphangioma of the ascending colon mesentery in an adult woman: clinical, radiological, and histopathological findings - Vermylen, Laurens; Pattyn, Paul (International Surgery Journal, 2025)
Cystic lymphangiomas are rare benign vascular lesions with lymphatic differentiation, most commonly diagnosed in childhood and typically located in the cervical and axillary regions. Intra-abdominal presentations are exceedingly uncommon in adults. We present the case of a 36-year-old woman with a large cystic lymphangioma arising from the mesentery of the ascending colon. Diagnosis was based on radiological imaging and confirmed by histopathological examination after surgical resection. This case highlights the diagnostic challenges and successful surgical management of a rare abdominal lymphatic malformation in an adult, discussed in the context of current literature.